Glass ceramic, preparation method thereof and glass product
By adjusting the composition distribution ratio and preparation process of microcrystalline glass, the problem of insufficient mechanical properties of traditional heat-resistant microcrystalline glass is solved, high heat resistance and excellent mechanical properties are achieved, and its application range is expanded.
Patent Information
- Application Number
- CN202411972286.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional heat-resistant microcrystalline glass has insufficient mechanical properties and overall strength in high temperature environments and cannot meet market demand.
By adjusting the composition distribution ratios of SiO2, Al2O3, Li2O, Na2O, K2O, ZrO2, TiO2, P2O5, B2O3, ZnO and MgO, and using specific preparation processes, including melting treatment, molding treatment, annealing treatment, chemical strengthening treatment and microcrystalization treatment, microcrystallation treatment were prepared.
It achieves high heat resistance and excellent mechanical properties of microcrystalline glass, meets the application requirements of glass products in high-strength protection, and expands the application range of microcrystalline glass.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass production and manufacturing, and in particular to a microcrystalline glass and a preparation method thereof, and a glass product. Background Art
[0002] With the development of modern electrical appliance industry, electrical consumer products such as induction cookers, electric ceramic cookers, integrated stoves, fireplaces and ovens have emerged. However, traditional stove panels such as induction cookers, electric ceramic cookers and integrated stoves, as well as high-temperature fire-resistant insulation board glass such as fireplaces and ovens have poor heat resistance and mechanical properties and cannot meet market demand.
[0003] Therefore, glass-ceramics were developed on the basis of traditional glass. They are multiphase complexes of dense microcrystalline phases and glass phases with high light transmittance. Most heat-resistant glass-ceramics products use lithium aluminum silicate system (Li2O-Al2O3-SiO2), and the main crystal phases are transparent β-quartz solid solution with zero or even negative expansion and milky white opaque β-spodumene solid solution with low expansion. Low expansion or even negative expansion can be achieved by adjusting the ratio of β-quartz solid solution and residual glass phase. However, since the expansion coefficient of the precipitated β-quartz solid solution is significantly lower than that of the matrix glass, circumferential tensile stress will be caused in the residual glass phase around the β-quartz solid solution, which is prone to stress concentration, significantly reducing the overall strength of the glass-ceramics and seriously affecting its application range.
[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention
[0005] Based on this, the present application provides a microcrystalline glass and a preparation method thereof, and a glass product. The microcrystalline glass of the present application has both high heat resistance and excellent mechanical properties.
[0006] This application is implemented through the following technical solutions:
[0007] In one aspect of the present application, a microcrystalline glass is provided, wherein the microcrystalline glass comprises the following components in terms of mass percentage: 54% to 66% SiO 2 、20%~30%Al 2 O 3 , 0.5%~3%Li 2 O, 0~5%MgO, 0~6%ZnO, 0~6%TiO 2 、1%~6%ZrO 2 , 0~5%P 2 O 5 , 0~3%B 2 O 3 , 0~2%BaO, 0.5%~3%Na 2 O and 0.1%~0.5%K 2O; where 4.5≤0.7P 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 ≤7, Na 2 O / K 2 O≥2; each oxide in the formula represents its mass percentage in the microcrystalline glass.
[0008] In some embodiments, the glass-ceramics comprises the following components, measured by mass percentage: 54% to 64% SiO 2 、21%~30%Al 2 O 3 , 1%~2%Li 2 O, 0~5%MgO, 0~6%ZnO, 0~6%TiO 2 、1%~6%ZrO 2 , 0~5%P 2 O 5 , 0~2%B 2 O 3 , 0~2%BaO, 0.5%~2.5%Na 2 O and 0.1%~0.5%K 2 O.
[0009] In some of these embodiments, the crystal phase of the glass-ceramics includes a quartz solid solution;
[0010] And / or, the crystal size of the glass-ceramics is 20nm~50nm;
[0011] And / or, the average crystallinity of the microcrystalline glass is ≤46%.
[0012] The microcrystalline glass of the present application comprises specific components with specific ratios, wherein SiO 2 Used to stabilize the network structure and main crystal phase formation of glass and glass ceramics; Al2O 3 It also stabilizes the network and provides improved mechanical properties and chemical durability. 2 O 3 It also ensures the formation of the main crystal phase. Alkali metal oxide Li 2 O、Na 2 O and K 2 O has the effect of lowering the melting temperature and improving the ion exchange capacity. ZrO 2 、TiO 2 and P 2 O 5 It is a common microcrystalline glass nucleating agent, which can induce the nucleation of basic glass by phase separation or enrichment condensation into micro-inhomogeneous areas.2 O 3 It can also promote phase separation and crystallization, while reducing the thermal expansion coefficient of the base glass and improving chemical resistance. ZnO also has the function of reducing high-temperature viscosity and increasing low-temperature viscosity. At the same time, ZnO can reduce the CTE of glass and improve the chemical stability and thermal stability of glass; MgO has a certain fluxing effect at high temperatures, and can also reduce the crystallization tendency and crystallization rate, and improve the chemical stability and mechanical strength of glass; a small amount of BaO can not only reduce the melting temperature of glass, but also improve the transparency of glass; by controlling 4.5≤0.7P at the same time 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 ≤7, Na 2 O / K 2 O≥2, so that the components work together in a specific ratio, making the microcrystalline glass have high heat resistance and excellent mechanical properties. When used in the preparation of glass products, it can meet the application requirements of high-strength protection of the products, thereby expanding the application scope of microcrystalline glass.
[0013] Furthermore, the preparation process of the microcrystalline glass is simple and easy to implement. By combining a specific composition ratio of the glass with a specific preparation process, microcrystalline glass with both high heat resistance and excellent mechanical properties can be obtained.
[0014] In one aspect of the present application, there is also a method for preparing glass-ceramics, comprising the following steps:
[0015] Providing raw materials according to the above-mentioned components of the glass-ceramics;
[0016] The raw materials are mixed and sequentially subjected to melting treatment, forming treatment and annealing treatment to prepare a matrix glass;
[0017] The base glass is subjected to chemical strengthening treatment and microcrystallization treatment in sequence to prepare microcrystalline glass.
[0018] In some embodiments, the temperature of the melting treatment is 1620° C. to 1720° C., and the time of the melting treatment is 4 h to 8 h.
[0019] In some embodiments, the annealing temperature is 600° C. to 700° C., and the annealing time is 1 h to 3 h.
[0020] In some of the embodiments, the chemical strengthening treatment comprises the following steps: placing the substrate glass in a mixed molten salt and treating it at a temperature of 400°C~460°C for 4h~20h; the mixed molten salt comprises lithium nitrate, sodium nitrate and potassium nitrate in a mass ratio of (1~10):(0~5):(85~99).
[0021] In some embodiments, the microcrystallization treatment includes sequentially subjecting the product after the chemical strengthening treatment to a nucleation treatment and a crystallization treatment;
[0022] Optionally, the temperature of the nucleation treatment is 680° C. to 780° C., and the time of the nucleation treatment is 1 h to 4 h;
[0023] Optionally, the temperature of the crystallization treatment is 850° C. to 950° C., and the time of the crystallization treatment is 0.5 h to 3 h.
[0024] In some embodiments, after the microcrystallization step, the following steps are further included:
[0025] The product after the microcrystallization treatment is cooled to 50°C~100°C at a cooling rate of 100°C / s~300°C / s.
[0026] One aspect of the present application further provides a glass product, which includes the above-mentioned microcrystalline glass or the microcrystalline glass produced by the above-mentioned method for producing microcrystalline glass. DETAILED DESCRIPTION
[0027] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0029] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0030] As shown in the background technology, in traditional technology, without changing the overall structure of the material, the most common strengthening technologies used in heat-resistant microcrystalline glass are chemical strengthening and physical strengthening. Through ion exchange or rapid cooling, a layer of compressive stress is formed on the surface of the glass, which can increase the strength of the material by 3 to 5 times, and significantly improve the mechanical properties of the material such as impact resistance and bending resistance. However, since the processing temperature of chemical strengthening is generally lower than 500°C, and the daily application temperature of low-expansion microcrystalline glass can reach 600°C to 700°C, at this temperature, the compressive stress generated on the surface of the material due to the "extrusion effect" will relax rapidly and lose the strengthening effect. Physical strengthening requires heating the material to near its softening point temperature, and then rapidly cooling it through a heat exchange medium (strong wind, water, etc.). Due to the difference in cooling and solidification rates inside and outside the material, surface compressive stress is generated to achieve a strengthening effect. However, the coefficient of thermal expansion (CTE) of crystallized low-expansion glass-ceramics is very low, and the deformation caused by temperature change is negligible, making it difficult to form surface compressive stress and achieve the strengthening effect; on the other hand, the softening point of low-expansion glass-ceramics is mostly over 900°C, far exceeding the upper limit of physical strengthening temperature; at the same time, the crystallization temperature of low-expansion glass-ceramics is generally above 850°C, and the material after physical tempering will also quickly produce stress relaxation at this temperature and lose the strengthening effect. In summary, the performance of traditional fire-resistant and heat-insulating glass is limited and cannot meet market demand.
[0031] Therefore, the technical personnel of this application obtained the technical solution of this application based on their own many years of research and development and actual production experience in this field and after a large number of creative experiments.
[0032] An embodiment of the present application provides a microcrystalline glass, which comprises the following components by mass percentage: 54% to 66% SiO 2 、20%~30%Al 2 O 3 , 0.5%~3%Li 2 O, 0~5%MgO, 0~6%ZnO, 0~6%TiO 2 、1%~6%ZrO 2, 0~5%P 2 O 5 , 0~3%B 2 O 3 , 0~2%BaO, 0.5%~3%Na 2 O and 0.1%~0.5%K 2 O; where 4.5≤0.7P 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 ≤7, Na 2 O / K 2 O≥2; each oxide in the formula represents its mass percentage in the microcrystalline glass.
[0033] The microcrystalline glass of the present application comprises specific components with specific ratios, wherein SiO 2 Used to stabilize the network structure of glass and glass ceramics and the formation of the main crystal phase; Al 2 O 3 It also stabilizes the network and provides improved mechanical properties and chemical durability. 2 O 3 It also ensures the formation of the main crystal phase. Alkali metal oxide Li 2 O、Na 2 O and K 2 O has the effect of lowering the melting temperature and improving the ion exchange capacity. ZrO 2 、TiO 2 and P 2 O 5 It is a common microcrystalline glass nucleating agent, which can induce the nucleation of basic glass by phase separation or enrichment condensation into micro-inhomogeneous areas. 2 O 3 It can also promote phase separation and crystallization, while reducing the thermal expansion coefficient of the base glass and improving chemical resistance. ZnO also has the function of reducing high-temperature viscosity and increasing low-temperature viscosity. At the same time, ZnO can reduce the CTE of glass and improve the chemical stability and thermal stability of glass; MgO has a certain fluxing effect at high temperatures, and can also reduce the crystallization tendency and crystallization rate, and improve the chemical stability and mechanical strength of glass; a small amount of BaO can not only reduce the melting temperature of glass, but also improve the transparency of glass; by controlling 4.5≤0.7P at the same time 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 ≤7, Na 2 O / K 2O≥2, so that the components work together in a specific ratio, making the microcrystalline glass have high heat resistance and excellent mechanical properties. When used in the preparation of glass products, it can meet the application requirements of high-strength protection of the products, thereby expanding the application scope of microcrystalline glass.
[0034] It is understood that when a numerical range is disclosed herein, the above range is considered continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0035] It should be noted that SiO 2 The value range of "54%~66%" is 55%~66% of the minimum and maximum values, and every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values in the embodiment and the following point values: 54%, 55%, 55.5%, 56%, 56.5%, 57%, 57.5%, 58%, 58.5%, 59%, 59.5%, 60%, 60.5%, 61%, 61.5%, 62%, 62.5%, 63%, 63.5%, 64%, 64.5%, 65%, 65.5% or 66%; or a range consisting of any two of these values, including, for example, 55%~60%.
[0036] SiO 2 It is an oxide involved in glass forming and can be used to stabilize the network structure of glass and glass ceramics. In some embodiments of the present invention, the glass or glass ceramic composition contains about 54-66 wt% SiO 2 In glass and glass ceramics, SiO 2 It is used as the main glass-forming oxide for base glass and one of the main oxides of the main crystalline phase, and can be used to stabilize the network structure of glass and glass ceramics and the formation of the β-quartz solid solution main crystalline phase. 2 Too high a content will lead to a significant increase in its melting temperature, making its production more difficult, and increasing unit energy consumption and carbon emissions; at the same time, the composition will also deviate greatly from the target crystal phase chemical composition, which is not conducive to the precipitation of β-quartz solid solution crystal phase.
[0037] Al 2 O 3The value range of "20%~30%" means the minimum and maximum values of the range of 20%~30%, and every value between the minimum and maximum values. Specific examples include but are not limited to 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5% or 30%; or a range consisting of any two of these values, as an example, including: 20%~29%.
[0038] Al 2 O 3 It also stabilizes the network and provides improved mechanical properties and chemical durability. 2 O 3 It is also one of the main oxides of the main crystal phase of β-quartz solid solution. In order to ensure the formation of the main crystal phase and the regulation of grain size, a certain content needs to be guaranteed. 2 O 3 The melting temperature is high, and as a network intermediate, it can often adjust Al 2 O 3 The amount of Al 2 O 3 Too high an amount of Al will generally increase the viscosity of the melt and reduce the glass-forming ability of the glass melt. In some embodiments, the glass or glass-ceramic composition may contain about 20-30 wt % Al 2 O 3 .
[0039] Li 2 The value range of O is "0.5%~3%", which means the minimum and maximum values in the range of 0.5%~3%, and every value between the minimum and maximum values. Specific examples include, but are not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%; or a range consisting of any two of these values, including, for example, 0.5%~2%.
[0040] Alkali Metal Oxides Li 2 O、Na 2 O and K 2 O has the function of lowering the melting temperature and improving the ion exchange capacity. 2O is one of the components of the β-quartz solid solution crystal phase and is indispensable. In addition, its ion radius is small and its electric field is strong. Within a certain content range, it is easy to accumulate in the glass network structure, which is conducive to the nucleation and growth of the lithium-containing crystal phase. If the content is too low, it cannot provide sufficient power for the precipitation of the target crystal phase. If the content is too high, it will suppress the exchange of Li in the molten salt with Na and K in the glass during the ion exchange process, making it difficult to form a gradient lithium content from high to low lithium content from the surface of the glass to the center. In some embodiments, the glass or glass ceramic composition may contain about 0.5-3wt% Li 2 O.Na 2 O and K 2 The content of O will also directly affect the concentration of ions on the glass surface after the ion exchange process. Since the K+ radius is greater than the Na+ radius and greater than the Li+ radius, in order to prevent the glass surface from cracking due to the large-radius ions replaced by the small-radius ions, it is necessary to limit the Na+ content. 2 O and K 2 O content, in some embodiments, the glass or glass ceramic composition may contain about 0.5-3 wt % Na 2 O and 0.1-0.5wt% K 2 O, and Na 2 O / K 2 O≥2.
[0041] The value range of MgO is "0~5%", which means that the minimum value and the maximum value in the range of 0~5% can be taken, as well as every value between the minimum value and the maximum value. Specific examples include, but are not limited to, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9% or 5.0%; or a range consisting of any two of these values, including, by way of example, 0.5% to 4%.
[0042] MgO has a certain fluxing effect at high temperatures, and can also reduce the crystallization tendency and crystallization rate, thereby improving the chemical stability and mechanical strength of the glass.
[0043] The value range of ZnO is "0-6%", which means the minimum and maximum values in the range of 0-6%, as well as every value between the minimum and maximum values. Specific examples include, but are not limited to, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%. , 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9% or 6%; or a range composed of any two of these values, as examples, including: 0.5% to 5%.
[0044] ZnO also has the function of reducing high-temperature viscosity and increasing low-temperature viscosity. At the same time, ZnO can reduce the CTE of glass and improve the chemical stability and thermal stability of glass.
[0045] TiO 2 The value range of is "0~6%", which means the minimum and maximum values in the range of 0~6%, as well as every value between the minimum and maximum values. Specific examples include, but are not limited to, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2% , 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9% or 6%; or a range composed of any two of these values, as examples, including: 0.5% to 5%.
[0046] ZrO 2The value range of is "1%~6%", which means the minimum and maximum values in the range of 1%~6%, as well as every value between this minimum and maximum value. Specific examples include, but are not limited to, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9% or 6%; or a range consisting of any two of these values, including, by way of example, 1.5% to 4%.
[0047] ZrO 2 、TiO 2 and P 2 O 5 It is a common microcrystalline glass nucleating agent, which can induce the nucleation of basic glass by phase separation or enrichment condensation into micro-inhomogeneous areas. 2 O 3 It can also promote phase separation and crystallization, while reducing the thermal expansion coefficient of the base glass and improving chemical resistance. However, in order to obtain samples with excellent mechanical and optical properties, it is necessary to control the crystallization process of the base glass, the grain growth rate should not be too fast, and the content of the above components needs to be regulated. In some embodiments, the glass or glass ceramic composition may contain about 1-6 wt% ZrO 2 、0-6wt%TiO 2 and 0-5wt%P 2 O 5 At the same time, the above components need to satisfy 4.5wt%≤0.7P 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 ≤7wt%.
[0048] P 2 O 5The value range of "0~5%" means that the minimum and maximum values in the range of 0~5% can be taken, as well as every value between this minimum and maximum value. Specific examples include, but are not limited to, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9% or 5%; or a range consisting of any two of these values, including, as examples, 1% to 4%.
[0049] B 2 O 3 The value range of "0~3%" is "0~3%", which means the minimum and maximum values in the range of 0~3%, and every value between the minimum and maximum values. Specific examples include, but are not limited to, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%; or a range consisting of any two of these values, as an example, including: 0.5%~3%.
[0050] The value range of BaO is "0~2%", which means the minimum and maximum values of the range of 0~2%, and every value between the minimum and maximum values. Specific examples include but are not limited to 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; or a range consisting of any two of these values, as an example, including: 0.5%~2%.
[0051] A small amount of BaO can not only lower the melting point of glass, but also improve the transparency of glass.
[0052] Na 2The value range of O is "0.5%~3%", which means the minimum and maximum values in the range of 0.5%~3%, and every value between the minimum and maximum values. Specific examples include, but are not limited to, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%; or a range consisting of any two of these values, including, for example, 0.5%~2%.
[0053] K 2 The value range of O is "0.1%~0.5%", which means that the minimum and maximum values in the range of 0.1%~0.5% can be taken, as well as every value between the minimum and maximum values. Specific examples include but are not limited to 0.1%, 0.2%, 0.3%, 0.4% or 0.5%; or a range consisting of any two of these values.
[0054] In addition, an appropriate amount of SnO can be added to the embodiment of the present invention. 2 , NaCl, NaNO 3 、CeO 2 Environmentally friendly clarifiers such as ferrous metal can help accelerate the melting and clarification of materials.
[0055] In some embodiments, the above-mentioned glass-ceramics includes the following components, measured by mass percentage: 54%-64% SiO 2 、21%~30%Al 2 O 3 , 1%~2%Li 2 O, 0~5%MgO, 0~6%ZnO, 0~6%TiO 2 、1%~6%ZrO 2 , 0~5%P 2 O 5 , 0~2%B 2 O 3 , 0~2%BaO, 0.5%~2.5%Na 2 O, 0.1%~0.5%K 2 O.
[0056] In some embodiments, the above 4.6≤0.7P 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 ≤6.8.
[0057] In some embodiments, the above 2≤Na 2 O / K 2 O≤23.
[0058] Furthermore, by controlling the composition ratio of the microcrystalline glass within the above-mentioned preferred range, the heat resistance and mechanical properties of the microcrystalline glass are better.
[0059] In some of the embodiments, the crystalline phase of the glass-ceramics includes a quartz solid solution.
[0060] In some of the embodiments, the grain size of the above-mentioned microcrystalline glass is 20nm~50nm.
[0061] In some of the embodiments, the average crystallinity of the above-mentioned microcrystalline glass is ≤46%.
[0062] An embodiment of the present application further provides a method for preparing microcrystalline glass, comprising the following steps S10 to S30.
[0063] Step S10: providing raw materials according to the above-mentioned components of the microcrystalline glass.
[0064] Step S20, mixing the above raw materials and sequentially performing melting treatment, molding treatment and annealing treatment to prepare precursor glass.
[0065] In some embodiments, the temperature of the melt treatment is 1620°C ~ 1720°C, for example, it can be 1620°C, 1625°C, 1630°C, 1635°C, 1640°C, 1645°C, 1650°C, 1655°C, 1660°C, 1665°C, 1670°C, 1675°C, 1680°C, 1685°C, 1690°C, 1695°C, 1700°C, 1705°C, 1710°C, 1715°C or 1720°C; in some examples, it can be within the range formed by any two of these point values as end values, the same below.
[0066] In some of the embodiments, the melting treatment time is 4 h to 8 h, for example, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h or 8 h.
[0067] In some embodiments, the annealing temperature is 600° C. to 700° C., and the annealing time is 1 h to 3 h.
[0068] Step S30, subjecting the precursor glass to chemical strengthening treatment and microcrystallization treatment in sequence to prepare microcrystalline glass.
[0069] The above-mentioned preparation method of microcrystalline glass is simple and easy to operate, can adapt to the existing production process, and can effectively reduce costs. The microcrystalline glass obtained by the above-mentioned preparation method has both excellent heat resistance and mechanical properties, and can meet the use requirements of glass products.
[0070] In some embodiments, the chemical strengthening step includes the following steps: placing the product after the annealing treatment in a mixed molten salt and treating it at a temperature of 400°C~460°C for 4h~20h; the mixed molten salt includes lithium nitrate, sodium nitrate and potassium nitrate in a mass ratio of (1~10): (0~5): (85~99).
[0071] In some embodiments, the mixed molten salt includes lithium nitrate, sodium nitrate and potassium nitrate in a mass ratio of (2-10): (0-4): (87-95).
[0072] In some embodiments, the temperature of the chemical strengthening treatment is 400°C~460°C, for example, it can be 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C, 450°C, 455°C or 460°C.
[0073] In some embodiments, the time of chemical strengthening treatment is 4h~20h, for example, it can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h or 20h.
[0074] It can be understood that, through the above-mentioned specific chemical strengthening treatment steps, the matrix glass is fully ion exchanged, and the lithium content decreases from the surface to the center of the glass, forming a gradient lithium content.
[0075] In some embodiments, the microcrystallization treatment comprises the following steps: subjecting the product after the chemical strengthening treatment to nucleation treatment and crystallization treatment in sequence.
[0076] In some embodiments, the temperature of the nucleation treatment is 680°C~780°C, for example, it can be 680°C, 685°C, 690°C, 695°C, 700°C, 705°C, 710°C, 715°C, 720°C, 725°C, 730°C, 735°C, 740°C, 745°C, 750°C, 755°C, 760°C, 765°C, 770°C, 775°C or 780°C.
[0077] In some embodiments, the time of the nucleation treatment is 1 hour to 4 hours, for example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.
[0078] In some embodiments, the temperature of the crystallization treatment is 850°C~950°C, for example, it can be 855°C, 860°C, 865°C, 870°C, 875°C, 880°C, 885°C, 890°C, 895°C, 900°C, 905°C, 910°C, 915°C, 920°C, 925°C, 930°C, 935°C, 940°C, 945°C or 950°C.
[0079] In some embodiments, the crystallization treatment time is 0.5 h to 3 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.
[0080] In some embodiments, after the above microcrystallization step, the following steps are further included:
[0081] The product after the above microcrystallization treatment is cooled to 50°C~100°C at a cooling rate of 100°C / s~300°C / s. For example, the cooling rate can be 100°C / s, 110°C / s, 120°C / s, 130°C / s, 140°C / s, 150°C / s, 160°C / s, 170°C / s, 180°C / s, 190°C / s, 200°C / s, 210°C / s, 220°C / s, 230°C / s, 240°C / s, 250°C / s, 260°C / s, 270°C / s, 280°C / s, 290°C / s or 300°C / s.
[0082] It is understandable that since the crystallinity of the precipitated β-quartz solid solution increases with the increase of lithium content, the CTE decreases with the increase of the crystallinity of the β-quartz solid solution, so that the surface with higher lithium content and lower CTE solidifies first during the rapid cooling process, while the interior with lower lithium content and higher CTE has not yet solidified, resulting in a compressive stress on the material surface in the interior with a tendency to shrink, achieving an effect similar to the physical tempering of glass.
[0083] Finally, the heat-resistant microcrystalline glass with self-strengthening is produced. The strengthening stress of the material is not released at low temperature. At this time, its surface compressive stress is the largest and the strengthening effect is the strongest. When the material is heated to 600℃~700℃ during the application process, part of the stress is released and relaxed, but because the crystallization temperature (850℃~950℃) is much higher than the application temperature, some strengthening compressive stress still exists, and when the material is cooled rapidly, due to the existence of gradient CTE, some strengthening compressive stress will also be generated autonomously.
[0084] One embodiment of the present application further provides a glass product, the glass product comprising the above-mentioned microcrystalline glass or microcrystalline glass produced by the above-mentioned method for preparing microcrystalline glass.
[0085] When the above-mentioned microcrystalline glass and its preparation method are used to prepare glass products, the heat resistance and mechanical properties of the glass products can be improved.
[0086] In some of the embodiments, the microcrystalline glass produced by the present application also has broad application prospects in astronomical telescopes, fire-proof glass, heat-resistant furnace window glass, high-temperature devices, chemical industry, electronics, navigation, exploration and military fields.
[0087] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
[0088] In order to better illustrate the present application, the contents of the present application are further described below in conjunction with embodiments.
[0089] Example 1
[0090] (1) According to the glass component formula shown in Table 1, the required raw materials are accurately weighed and mixed uniformly to obtain a mixture.
[0091] (2) Place the mixed raw materials in a platinum crucible and melt them at 1620°C~1720°C for 4-8 hours while stirring with a platinum stirring paddle. After the stirring paddle is removed, cool the temperature to 1500~1600°C and keep it at this temperature for 2 hours to homogenize and obtain a molten liquid.
[0092] (3) The molten liquid is cast onto an iron mold to form a glass block of about 200*200 mm in size. The mold is preheated to 500°C before casting. After the glass block hardens, it is immediately transferred to an annealing furnace for annealing. The temperature is kept for 2 hours, then the temperature is reduced by 140°C in 6 hours, and it is naturally cooled. After being taken out, it is set aside to obtain the precursor glass.
[0093] (4) The precursor glass is cut into glass sheets of 200*200*4.3 mm by Shenyang Kejing's STX-1203 wire cutting machine, thinned and polished to about 4 mm by a double-sided grinding and polishing machine, and then edged by a CNC engraving machine to obtain the finished glass.
[0094] (5) The processed glass is placed in a tempering furnace for ion exchange treatment: the processed glass is treated with a mixed molten salt of lithium nitrate (1% to 10%), sodium nitrate (0 to 5%) and potassium nitrate (85% to 99%), and hot-dipped at 400°C to 460°C for 4h to 20h, so that the processed glass is fully ion-exchanged to obtain ion-exchanged glass, in which the lithium content decreases from the surface to the center of the glass, forming a gradient lithium content.
[0095] (6) The ion-exchanged glass is subjected to microcrystallization treatment in a Nabertherm crystallization furnace: the first step is nucleation treatment at 680°C~780°C for 1h~4h, and the second step is crystallization treatment at 850°C~950°C for 0.5h~3h. After the microcrystallization treatment, the sample is immediately cooled quickly and uniformly by strong wind, running water or other media (cooling rate 100°C / s~300°C / s) to obtain microcrystalline glass.
[0096] (7) The physical and chemical properties of the prepared glass-ceramics are tested. The following are the specific performance tests.
[0097] 1. Use Lambda950 UV-visible spectrophotometer from PerkinElmer, USA to test the transmittance in the wavelength range of 380-780nm, referring to GB / T 2680-1994 standard for details.
[0098] 2. Grind the above samples into powder and pass through a 200-mesh sieve. Use Bruker's X-ray diffractometer Bruker D8advance to test its crystal phase type, and use its TOPAS software to simulate and calculate the proportion of different types of crystal phases and amorphous phases. Specifically, press the 200-mesh microcrystalline glass powder on the concave surface of the glass sample holder. The XRD scanning angle is 10°~90° and the scanning time is 12 minutes.
[0099] 3. Use Dongguan Puset PT-706 falling ball tester to test the falling ball impact resistance height.
[0100] 4. Japan Orihara Industries Co., Ltd. FSM-6000LE tests the surface toughening compressive stress. Specifically, the microcrystalline glass plate is placed on the test prism, and the refractive liquid uses a refractive index of 1 to 1.49 to test the physical toughening stress of the sample.
[0101] 5. Shenzhen Bonabond BND-T106 spring impact hammer tests the impact energy. Specifically, a spring impactor is used to perform impact tests on three points of the microcrystalline glass plate, with each point impacted three times.
[0102] 6. Thermal shock resistance test: place the microcrystalline panel in a high temperature environment corresponding to the test temperature, and after reaching thermal equilibrium (about 30 minutes), take it out and quickly put it into normal temperature water. This is considered as a cycle, and the test is carried out for 3 cycles; record it in the table.
[0103] Embodiments 2 to 12
[0104] The preparation methods of the glass-ceramics of Examples 2 to 12 are basically the same as those of Example 1, and the only difference is the components and parameters in Tables 1 and 2.
[0105] Other conditions and parameters are the same as those in Example 1. Please see Table 1 and Table 2 for specific test results.
[0106] Comparative Examples 1 to 4
[0107] The preparation methods of the glass-ceramics of Comparative Examples 1 to 4 are basically the same as those of Example 1, with the only difference being that the raw material formulas and process parameter conditions of the glass in Comparative Examples 1 to 4 are as shown in Table 3.
[0108] Other conditions and parameters are the same as those in Example 1. Please see Table 3 for specific test results.
[0109] Comparative Example 5
[0110] The preparation methods of the microcrystalline glass of Comparative Example 5 and the embodiment are basically the same, except that: in Comparative Example 5 (5), the above-mentioned finely processed glass is first subjected to microcrystallization treatment and then to chemical strengthening treatment to obtain microcrystalline glass.
[0111] Other conditions and parameters are the same as those in Example 1. Please see Table 3 for specific test results.
[0112] Table 1
[0113]
[0114] Table 2
[0115]
[0116] Table 3
[0117]
[0118] Note: “ / ” indicates that the component does not exist.
[0119] Combined with the data in Table 1 to Table 3, the self-strengthened heat-resistant microcrystalline glass obtained in Example 1 to Example 12, through reasonable material design and the above preparation and treatment processes, has an average crystallinity of ≤46%, heat shock resistance ∆T≥800℃, and a 4mm thick microcrystalline glass has a strengthened compressive stress of 5MPa~30MPa at room temperature, a 535g steel ball impact height of ≥1m, and an impact hammer impact energy of ≥0.7J.
[0120] Comparative Example 1 Compared with Example 1, SiO 2 Low content, Al 2 O 3The content is high, and 0.7P 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 >7, it is difficult to precipitate the target crystal phase of β-quartz solid solution, and its grain size is difficult to control, which leads to a significant decrease in the transmittance of the sample and affects the ion exchange process. The surface compressive stress is extremely low, resulting in reduced mechanical properties against falling ball impact, impact hammer impact, and thermal shock resistance.
[0121] Comparative Example 2 Compared with Example 1, SiO 2 High content, Al 2 O 3 The content is low, the target crystal phase of β-quartz solid solution is difficult to precipitate, and its grain size is difficult to control, resulting in a decrease in the transmittance of the sample; Na 2 O / K 2 O<2, Na in the sample 2 The relative low content of O makes it difficult to form a good gradient Li during the ion exchange process. 2 O content and extremely low surface compressive stress result in poor mechanical properties against falling ball impact, impact hammer impact and thermal shock resistance.
[0122] Comparative Example 3 Compared with Example 1, Li 2 The high O content makes it difficult to form a gradient Li during the ion exchange process. 2 O content makes it difficult to form a gradient CTE during the crystallization heat treatment process, and the surface stress is extremely low, resulting in poor mechanical properties against falling ball impact and impact hammer impact.
[0123] Comparative Example 4: Al 2 O 3 The content is low, TiO 2 The content is too high and 0.7P 2 O 5 +0.5B 2 O 3 +ZrO 2 +TiO 2 >7, resulting in the matrix glass being 2 The coloring is serious, the transmittance is reduced, and it is difficult to control the grain size and its crystallinity during the crystallization process. The transmittance of the sample is greatly reduced after crystallization, and its thermal shock resistance is also reduced.
[0124] Compared with Example 1, Comparative Example 5 first performs crystallization treatment and then performs ion exchange; first, the ion exchange capacity of the crystallized sample deteriorates due to the presence of the crystal phase, and the ideal ion exchange effect cannot be obtained; secondly, the sample fails to form a crystal phase distribution and structure with a gradient CTE, and cannot generate surface compressive stress, resulting in poor mechanical properties against falling ball impact and impact hammer impact.
[0125] Compared with the microcrystalline glass prepared in the comparative example, the microcrystalline glass prepared according to the technical solution of the present application has excellent heat resistance and comprehensive mechanical properties, and can meet the practical application of the product.
[0126] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0127] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A glass-ceramic, characterized in that: The microcrystalline glass comprises the following components in percentage by mass: 54% to 66% SiO2, 20% to 30% Al2O3, 0.5% to 3% Li2O, 0 to 5% MgO, 0 to 6% ZnO, 0 to 6% TiO2, 1% to 6% ZrO2, 0 to 5% P2O5, 0 to 3% B2O3, 0 to 2% BaO, 0.5% to 3% Na2O and 0.1% to 0.5% K2O; Among them, 4.5≤0.7P2O5+0.5B2O3+ZrO2+TiO2≤7, Na2O / K2O≥2; each oxide in the formula represents its mass percentage in the microcrystalline glass.
2. The glass-ceramic according to claim 1, characterized in that: In terms of mass percentage, the microcrystalline glass includes the following components: 54%~64% SiO2, 21%~30% Al2O3, 1%~2% Li2O, 0~5% MgO, 0~6% ZnO, 0~6% TiO2, 1%~6% ZrO2, 0~5% P2O5, 0~2% B2O3, 0~2% BaO, 0.5%~2.5% Na2O and 0.1%~0.5% K2O.
3. The glass-ceramics according to any one of claims 1 to 2, characterized in that: The crystal phase of the glass-ceramics includes a quartz solid solution; And / or, the crystal size of the glass-ceramics is 20nm~50nm; And / or, the average crystallinity of the microcrystalline glass is ≤46%.
4. A method for preparing glass-ceramics, characterized in that: The steps include: Providing raw materials according to the components of the glass-ceramics according to any one of claims 1 to 3; The raw materials are mixed and sequentially subjected to melting treatment, forming treatment and annealing treatment to prepare a matrix glass; The base glass is subjected to chemical strengthening treatment and microcrystallization treatment in sequence to prepare microcrystalline glass.
5. The method for preparing glass-ceramics according to claim 4, characterized in that: The temperature of the melting treatment is 1620° C. to 1720° C., and the time of the melting treatment is 4 h to 8 h.
6. The method for preparing glass-ceramics according to claim 4 or 5, characterized in that: The temperature of the annealing treatment is 600° C. to 700° C., and the time of the annealing treatment is 1 h to 3 h.
7. The method for preparing glass-ceramics according to claim 4 or 5, characterized in that: The chemical strengthening treatment comprises the following steps: placing the substrate glass in a mixed molten salt and treating it at a temperature of 400° C. to 460° C. for 4 h to 20 h; the mixed molten salt comprises lithium nitrate, sodium nitrate and potassium nitrate in a mass ratio of (1 to 10): (0 to 5): (85 to 99).
8. The method for preparing glass-ceramics according to claim 4 or 5, characterized in that: The microcrystallization treatment includes sequentially subjecting the product after the chemical strengthening treatment to a nucleation treatment and a crystallization treatment; Optionally, the temperature of the nucleation treatment is 680° C. to 780° C., and the time of the nucleation treatment is 1 h to 4 h; Optionally, the temperature of the crystallization treatment is 850° C. to 950° C., and the time of the crystallization treatment is 0.5 h to 3 h.
9. The method for preparing glass-ceramics according to claim 4 or 5, characterized in that: After the microcrystallization step, the method further comprises the following steps: The product after the microcrystallization treatment is cooled to 50°C~100°C at a cooling rate of 100°C / s~300°C / s.
10. A glass product, characterized in that: The glass product comprises the microcrystalline glass as described in any one of claims 1 to 3 or the microcrystalline glass prepared by the method for preparing microcrystalline glass as described in any one of claims 4 to 9.
Citation Information
Patent Citations
Preparation of glass-ceramics of beta-quartz and / or of beta-spodumene, of articles made from such glass-ceramics, glass-ceramics, articles made from said glass-ceramics and precursor glasses
CN101213152A
Li2o-Al2o3-Sio2 based crystallised glass and production method for same
CN102933516A
Transparent beta-quartz glass-ceramics with a low lithium content
CN113015709A
Li2o-al2o3-sio2-based crystallized glass
CN113710624A
Transparent beta-quartz glass ceramics with specific transmittance
CN115551814A